Implications of a pervasive climate model bias for low-cloud feedback - Ceppi,P; Myers,TA; Nowack,P; Wall,CJ; Zelinka,MD (Geophysical Research Letters, 2024)
How low clouds respond to warming constitutes a key uncertainty for climate projections. Herewe observationally constrain lowcloud feedback through a controlling factor analysis based on ridgeregression. We find a moderately positive global lowcloud feedback (0.45 W m− 2 K− 1, 90% range 0.18–0.72 Wm− 2 K− 1), about twice the mean value (0.22 W m− 2 K− 1) of 16 models from the Coupled ModelIntercomparison Project. We link this discrepancy to a pervasive model meanstate bias: models underestimatethe lowcloud response to warming because (a) they systematically underestimate presentday tropical marinelowcloud amount, and (b) the lowcloud sensitivity to warming is proportional to this presentday lowcloudamount. Our results hence highlight the importance of reducing model biases in both the mean state of cloudsand their sensitivity to environmental factors for accurate climate change projections